Sex differences in human performance - Hunter, S. K.; Senefeld, J. W. (The Journal of Physiology, 2024)
Sex as a biological variable is an underappreciated aspect of biomedical research, with its importance emerging in more recent years. This review assesses the current understanding of sex differences in human physical performance. Males outperform females in many physical capacities because they are faster, stronger and more powerful, particularly after male puberty. This review highlights key sex differences in physiological and anatomical systems (generally conferred via sex steroids and puberty) that contribute to these sex differences in human physical performance. Specifically, we address the effects of the primary sex steroids that affect human physical development, discuss insight gained from an observational study of `real-world data` and elite athletes, and highlight the key physiological mechanisms that contribute to sex differences in several aspects of physical performance. Physiological mechanisms discussed include those for the varying magnitude of the sex differences in performance involving: (1) absolute muscular strength and power; (2) fatigability of limb muscles as a measure of relative performance; and (3) maximal aerobic power and endurance. The profound sex-based differences in human performance involving strength, power, speed and endurance, and that are largely attributable to the direct and indirect effects of sex-steroid hormones, sex chromosomes and epigenetics, provide a scientific rationale and framework for policy decisions on sex-based categories in sports during puberty and adulthood. Finally, we highlight the sex bias and problem in human performance research of insufficient studies and information on females across many areas of biology and physiology, creating knowledge gaps and opportunities for high-impact studies.